IMPROVING STUDENTS' READING COMPREHENSION ACHIEVEMENT BY USING DR-TA STRATEGY (DIRECTED READING-THINKING ACTIVITY) AT SMP NEGERI 3 - Hasan Sadiqin (Pusat Studi Pendidikan Bahasa Inggris Fakultas Ilmu Tarbiyah dan Keguruan Universitas Negeri Raden Fatah Palembang, 2016)
The objective of this study is to find out whether or not there is a significant difference on students' reading comprehension achievement between the students who were taught by using DR-TA strategy and those who were taught by using teachers' strategy at the second year students of SMP Negeri 3 Palembang. This research was conducted through quasi-experimental method and used nonequivalent control group design. The population was 458 students of the second year of SMP Negeri 3 Palembang in the academic year 2013/2014. Seventy four students were chosen as the sample by using convenience sampling technique. The sample was assigned into two groups; the experimental group and the control group. Each group consisted of thirty seven students. The data were obtained by multiple choice tests. A test was given both to the experimental and control groups but only one group given treatment. The result of the test was analyzed by means of SPSS 16. Based on the result of the data analysis that is the result of hypothesis testing using independent sample t-test, the significant difference was found the p-output (0.000) lower than 0.05. It means that, there was a significant difference between students' pretest and posttest scores in experimental group taught using DR-TA strategy. Therefore, it can be concluded that DR-TA strategy was significantly improved. The writer also found that most of the students of both groups made a good reading improvement. However, there were still some students who were poor in reading comprehension achievement.